PERBANDINGAN METODE PELAKSANAAN BETON KONVENSIONAL DENGAN PRA CETAK TERHADAP BIAYA DAN WAKTU (STUDI KASUS : PEKERJAAN DRAINASE PROYEK PEMBANGUNAN JALAN TOL BALIKPAPAN – SAMARINDA SEKSI 4) - CAINAWA, RAJA (KURVA S JURNAL MAHASISWA, 2020)
Conventional concrete in its manufacture is published in advance, all concrete work is manually designed by stringing reinforcement in buildings that are made. Precast concrete is produced from the production process where the manufacturing location is different from the location where structural elements will be used. And the location of drainage works research for Balikpapan - Samarinda toll road construction section 4. The results of the analysis of conventional concrete implementation methods require a fee of Rp. 408.202.900, - and requires implementation time of 40 days. The results of the analysis of precast concrete implementation methods require a fee of Rp. 461.453.700, - and requires implementation time for 35 days.